Analisis Jarimah Judi Online Dalam Perspektif Fiqh Jinayah - Ningsih, Febri Adelia; Sumantri, Sonya Noprisa; Fachri, Syacharani Aulia; Sabrina, Shafiyah; Setiawan, Aga; Al Ghaffar, Syahly Luthfie (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2025)
The development of digital technology has had a significant impact on various aspects of life, including gambling practices. Online gambling, as a form of gambling carried out through a digital platform, has become one of the social problems that continues to grow in many countries, including in countries with a Muslim majority population. This study aims to analyze online gambling crimes from the perspective of Islamic jurisprudence, which examines Islamic criminal law related to gambling crimes. This study discusses the basic concept of Islamic jurisprudence regarding gambling, as well as various views of scholars related to online gambling laws that can be considered as one form of crime. In addition, this study also analyzes the types of punishments that can be applied based on the provisions of Islamic jurisprudence, such as hudud, ta'zir, and other preventive measures. Through a qualitative approach with a normative descriptive analysis method, this study identifies factors that influence the spread of online gambling, its impact on individuals and society, and legal solutions that can be applied to overcome this phenomenon. The results of this study are expected to provide insight for policy makers and the community regarding the need to strengthen legal regulations in accordance with Islamic principles in overcoming online gambling crimes.